Gymnastēs. Pugilato tra metodologia e filosofia - De Donato, Renato (Milano University Press, 2023)
This work thoroughly explores the world of boxing from an interdisciplinary perspective. Building upon the text of "gymnasticus" written by the rhetorician Lucius Flavius Philostratus, the author develops an innovative methodological hypothesis, involving the disciplines of philosophy, history, and cognitive and motor sciences. Through a philosophical analysis of contemporary authors such as Hadot, Foucault, and Deleuze, the author incorporates their insights and applies them to the current context of sports science. The main objective is to overcome the mind-body dualism, fully recognizing the emotional and desirous aspects in boxing practice. This volume aspires to provide the foundations for future research in the field of athlete training and development.